Positioning, transfer, and rotation movements of particles manipulated by a novel piezoelectric acoustofluidic device with multiple vibration modes. (9th September 2021) - Feng, Haoren; Wang, Liang; Wang, Xin; Jin, Jiamei
Abstract: Acoustic-based manipulation platforms are the preferred device to manipulate particles in analytical chemistry and biomedicine due to their label-free and high biocompatibility. As a significant wave mode of the acoustic manipulation method, bulk acoustic waves (BAWs) have been wildly concerned by academia and industry. To realize the high-precise multi-mode manipulation of particles with a simple structure, a BAWs-based piezoelectric acoustofluidic device is proposed. It is composed of a Langevin transducer and a disk with a circular groove. Two vibration modes of the disk with three and five node circles, respectively, are used to manipulate particles to position, transfer, and rotate. A non-nodal acoustic trap is induced in the disk center by producing its first out-of-plane bending vibration mode. In this acoustic trap, the spherical particles and irregularly shaped particles can be fixed entirely and rotated, respectively. Simultaneously, the disk center is an antinode of the acoustic field induced by the second disk out-of-plane bending vibration mode, leading to that the trapped particles can be equidistantly transferred from the disk center to the nearest node. The effectiveness of the proposed device is verified by simulations and experiments. With appropriate control parameters, the minimum position fluctuation of the submillimeter-hollow-glass sphere (SHGS) after being positioned is 0.32% of its diameter. Moreover, the maximum transfer speed of the SHGS and maximum rotation speed of the cylindrical metal wire are 130.8 mm s −1 and 23.51 rad s −1, respectively. This proposed device is capable of multiple manipulation modes for particles with simple control strategy, providing a novel method for designing a BAWs-based device to achieve the manipulation of particles.